A vida como viagem: a navegação de São Brandão e a busca do paraíso - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
The Navigation of St. Brendan is known as a branch of medieval Latin texts, which bring the story of the sea voyage of St. Brendan and his monks in search of "terra repromissionis", an lost paradise insular. In the narrative, Brendan and his companions traveling for seven years in a wonderful space, where they meet many wonderful islands. Along the way, they celebrate the major feasts of the liturgical calendar (Easter and Christmas), annually reliving the life and death of Jesus. The journey is marked by numerous wonders, but also by many dangers and difficulties, and should be placed within the context of medieval belief in the afterlife and representation of earthly life as a pilgrimage. Thus, every man was basically a stranger walking through this world to reach their eternal abode. Thus, the search for Paradise by St. Brendan can be seen as a representation of the medieval Christian journey in search of salvation. This journey culminates with their entry into Paradise, where all the righteous could finally enjoy a full happiness and enjoy the rewards of a virtuous life.
Keywords: Narrativa; Paraíso; Viagem marítima - São Brandão; CIÊNCIAS HUMANAS: HISTÓRIA